Pengaruh Metode Student Created Case Studies Berbantuan Flip Chart terhadap Tingkat Kemandirian dan Hasil Belajar Biologi: The Effect of The Student Created Case Studies Method Assisted by Flip Charts on The Level of Independence and Learning Outcomes of Biology - Anak Agung Sagung Wisakka Arundhati; I Nengah Suka Widana; Edy Hermawan (FPMIPA IKIP PGRI Bali, 2019)
The purpose of the study was to determine the effect of the student created case studies method assisted by flip charts on the level of independence and learning outcomes of biology. The research is classified as a quasi-experimental, using Nonequivalent Control Group Design. The population consisted of all students of class X MIPA SMA 1 Blahbatuh, consisting of 7 classes (278 students). Samples were taken in simple random order, obtained 80 students of class X MIPA2 and X MIPA5. Biology learning independence score data are used questionnaires and learning outcomes scores (grades) using learning outcomes test instruments. Hypothesis testing using t-test and Manova. Based on data analysis, the following are found: 1) there are differences in the level of independence between students, following a student created case study method assisted by flip charts by following conventional learning, 2) there are differences in biology learning outcomes of students following a student created case study method assisted by flip charts by following conventional learning, 3) there are simultaneous differences in the level of independence and biology learning outcomes between those who attend a student created case study method assisted by flip charts with those who follow conventional learning.